(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article explores the phonostatistics of the Leilek dialect, based on the collection of works «El Ichi - Önör Kenchi», which includes pieces by masters of song and storytelling arts. This study discusses the general phonostatistics of the Leilek dialect.